PHF20 positively regulates osteoblast differentiation via increasing the expression and activation of Runx2 with enrichment of H3K4me3 - Jin-Woo Yang (Nature Portfolio, 2017)
Abstract Plant homeodomain finger protein 20 (PHF20), a methyl lysine effector protein, is a component MOF-NSL lysine acetyltranferase complex. Global deletion of PHF20 has shown spinal bone defects and reduced skeletal formation. However, the molecular basis of PHF20 involved in skeletal development has not been elucidated yet. The objective of this study was to determine the role of PHF20 in osteoblast differentiation and mineralization. Expression of PHF20 was gradually increased during osteoblast differentiation. Overexpression of PHF20 enhanced ALP activity and mineralized nodule formation as well as the expression of osteogenic markers including Runx2. In contrast, inhibition of PHF20 expression reduced osteoblast differentiation and mineralization. Mechanistically, PHF20 increased the promoter activity of osteogenic genes including Og2, Alp, and Bsp through direct association with Runx2. Moreover, PHF20 increased the enrichment of H3K4me3 on the promoter of Runx2 followed by increased Runx2 promoter activity. Interestingly, Bix-01294, a histone methylation inhibitor, decreased mineralized nodule formation through decreasing the levels of H3K4me3 and Runx2. Overexpression of PHF20 restored the Bix-01294 effects. Taken together, these results indicate that methyl lysine-binding protein PHF20 might be a novel regulator of osteoblast differentiation.